2009
DOI: 10.1017/s1368980008002516
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetables are similarly categorised by 8–13-year-old children

Abstract: Objective: This exploratory study assessed how 8-13-year-old children categorised and labelled fruit and vegetables (FaV), and how these were influenced by child characteristics, to specify second-level categories in a hierarchical food search system for a computerised 24 h dietary recall (hdr). Design: Two sets of food cards, sixty-seven for fruit (F) and sixty-four for vegetables (V), with pictures and names of FaV from ten professionally defined food categories were sorted, separately, by each child into pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…7,8 For children, having child-generated food categories, 9-11 pictures of foods, 12 and different sizes of food images on the same screen 13 may help improve recall speed and/or accuracy. 14 Examples of computerized 24hDRs include the Food Intake Recording Software System (FIRSST), 15,16 the Young Adolescents’ Nutrition Assessment on Computer (YANA-C), 8,17,18 and the Automated Self-Administered 24-hour Dietary Recall for children (ASA24-Kids).…”
Section: Introductionmentioning
confidence: 99%
“…7,8 For children, having child-generated food categories, 9-11 pictures of foods, 12 and different sizes of food images on the same screen 13 may help improve recall speed and/or accuracy. 14 Examples of computerized 24hDRs include the Food Intake Recording Software System (FIRSST), 15,16 the Young Adolescents’ Nutrition Assessment on Computer (YANA-C), 8,17,18 and the Automated Self-Administered 24-hour Dietary Recall for children (ASA24-Kids).…”
Section: Introductionmentioning
confidence: 99%
“…Methods similar to those used in this study were applied to different groups of food items: mixed foods (19), fruit and vegetables (20), and grain foods (21). Inter study comparisons revealed Script and Taxonomic categories were also the most used in the other reports, but in the case of the Mixed dishes study, Specific Foods was the second most commonly used category (19).…”
Section: Discussionmentioning
confidence: 99%
“…Children classified and labeled foods depending on the context of other foods in the set. For example, corn was categorized under Meal (lunch or dinner) in this card sort and under Vegetables when grouped in a Mixed Dishes (19) card sort, and in a vegetable sub category in a Vegetable card sort (20). Milk was categorized in Drinks in this card sort, but Dairy in the Mix Dishes card sort (19).…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of this technique include restricting the participants to the items listed in the card deck, a lack of in-depth of information about the item placement in the categories, and the exclusion of illiterate participants when words are used (Weller and Romney, 1988). Examples of card sorts within food research include assessing diet and understanding how adults and children categorize food (Beltran et al, 2008;Blake et al, 2007;Lynch and Holmes, 2011;Sepulveda et al, 2009;Sherwood et al, 2003).…”
Section: Measurementmentioning
confidence: 99%